Fraudulence Financial Statements Analysis using Pentagon Fraud Approach - Triyanto, Dedik Nur (Universitas Padjadjaran, 2019)
This study aims to examine the influence of variables, namely pressure, opportunity, rationalization, competence, and arrogance on fraudulent financial statements of companies listed in Indonesia Stock Exchange. The subject of the study is the food and beverage manufacturing firms. The period of investigation is the year 2015 – 2017. This study used purposive sampling technique. In total, there are 36 foods and beverage manufacturing firms involved in this study. The data was generated from the firm’s annual report using a content analysis approach. Panel data of 36 foods and beverage for three years (2015 – 2017) was used for analyzing. The analysis model employed in this study is multiple regression. The results indicate that variable namely, pressure, opportunity, rationalization, competence, and arrogance, simultaneously do not affect fraudulence financial statement. Partially, only competence variable significantly affect fraudulence financial statement. It implies that the pentagon theory of fraud is not applicable to understand fraudulence financial statement in the context listed manufacturing firms of food and beverage in Indonesia.